Vessel Patterning in the Embryo of the Zebrafish: Guidance by Notochord - Fouquet, Bernadette; Weinstein, Brant M.; Serluca, Fabrizio C.; Fishman, Mark C. (Developmental biology, 1997)
We have cloned the zebrafish homolog of the receptor tyrosine kinaseflk-1to provide us with a tool to study normal vascular pattern formation in the developing zebrafish embryo and to compare it to mutants in which vascular pattern is perturbed. We find that during normal development the first angioblasts arise laterally in the mesoderm and then migrate medially to form the primordia of the large axial vessels, the dorsal aorta (axial artery) and the axial vein. Lumen formation occurs shortly before onset of circulation at 24 hr postfertilization. We examined the specification of vascular progenitors in the mutantcloche,which fails to form both vessels and blood.clochelacks allflk-expressing cells and therefore appears to lack angioblasts. The axial vessels of the trunk form in close proximity to notochord and endoderm, which may provide cues for their formation. The dorsal aorta is normally just ventral to the notochord; the axial vein is just below the dorsal aorta and above the endoderm.floating head (flh)andno tail (ntl)mutants both have defects in the formation of notochord. Both are cell-autonomous lesions,flhabolishing notochord andntlpreventing its differentiation. In both mutants the dorsal aorta fails to form, while formation of the axial vein is less affected. Mosaic analysis of mutant embryos shows that transplanted wild-type cells can become notochord in mutantflhembryos. In these mosaic embryosflhcells expressingflkassemble at the midline, beneath the wild-type notochord, and form an aortic primordium. This suggests that signals from the notochord may guide angioblasts in the fashioning of the dorsal aorta. The notochord seems to be less important for the formation of the vein.